A systematic study of the genus Dinera Robineau-Desvoidy from the Palaearctic and Oriental regions (Diptera: Tachinidae) - Zhang, Chun-Tian; Shima, Hiroshi (Zootaxa, 2006)
The genus Dinera Robineau-Desvoidy from the Palaearctic and Oriental regions is revised; six described species are recognized, viz. D. carinifrons (Fallén), D. ferina (Fallén), D. grisescens (Fallén), D. longirostris Villeneuve, D. miranda (Mesnil) and D. takanoi (Mesnil), and 12 species are described as new to science: D. alticola, D. angustifrons, D. brevipalpis, D. chaoi, D. fuscata, D. maculosa, D. meridionalis, D. orientalis, D. setifacies, D. sichuanensis, D. similis and D. xuei. A key to the 18 species of Dinera and 66 diagnostic figures of the male terminalia are given.